Perceptions from undergraduate nursing students about finitude in hospitals - Santana, Julio César Batista; Leal, Anna Carolina; Lopes, Priscilla Almeida Torres; Guimarães, Renata Gomes; Holanda, Tássila Silva Melo de; Dutra, Bianca Santana (Revista de Enfermagem UFPE on line, 2009)
ABSTRACT Objective: understanding the process of death and dying in hospitals in the perception of undergraduate nursing students. Methodology: this is about a qualitative study, from phenomenological approach, performed of seven nursing students at the University José Rosário Vellano. The research project has been approved by the Ethics Committee in Research of the University José Rosário Vellano (protocol number 76/2009). Results: through the interviews was enabled the construction of five categories: 1) Thinking about death, experiencing anxiety, 2) Professionalism in the view of academics and involvement with the cases, 3) The psychological impact at the time of loss and 4) The importance of family care of the patient; 5) Understanding the need to discuss death in academic education. Conclusion: the results showed that the students feel unprepared to deal with death, demonstrating a degree of anxiety, insecurity to talk about it, this is because the discussion of this issue is not frequent in the graduation, we believe that the creation of spaces for self-knowledge, awareness and reflection on the theme of death in the universities, would allow the training of professionals not only able to watch life for the rehabilitation or cure, but also prepared to deal with death. Descriptors: death; right to die; education; nursing. RESUMO Objetivo: compreender o processo da morte e do morrer nos hospitais na percepção de acadêmicos de enfermagem. Metodologia: estudo qualitativo, de abordagem fenomenológica, com sete graduandos de enfermagem da Universidade José Rosário Vellano. O Projeto de Pesquisa que foi aprovado pelo parecer n°. 76/2009 do Comitê de Ética da referida Universidade. Resultados: a análise das falas possibilitou a elaboração de cinco categorias: 1) Pensando na morte, vivenciando a angústia; 2) Profissionalismo na visão dos acadêmicos e o envolvimento com os casos; 3) O impacto psicológico no momento da perda; 4) A importância da assistência à família do paciente; 5) Compreendendo a necessidade de discutir a morte na formação acadêmica. Conclusão: os resultados evidenciaram que os acadêmicos se sentem despreparados para lidar com a morte, demonstrando uma certa angústia, insegurança ao falar sobre o assunto, isso se deve ao fato da discussão dessa temática não ser freqüente dentro da graduação, entendemos que a criação de espaços para autoconhecimento, sensibilização e reflexão sobre o tema morte nas universidades, possibilitaria a formação de profissionais não só capacitados para assistir a vida visando a reabilitação ou a cura, mas também preparados para lidar com a morte. Descritores: morte; direito a morrer; educação em enfermagem. RESUMEN Objetivo: comprender el proceso de morir y la muerte en los hospitales de la percepción de estudiantes de enfermería. Metodología: estudio cualitativo, de enfoque fenomenológico. Participaron en el estudio, siete estudiantes de enfermería de la Universidad José Rosario Vellano después que lo proyecto de investigación fue aprobado por el Comité de Ética (número del registro 76/2009). Resultados: el análisis de las declaraciones permitieron la construcción de cinco categorías: 1) Pensar en la muerte, experimentan ansiedad, 2) La profesionalidad en el punto de vista de los académicos y la participación de los casos, 3) El impacto psicológico en el momento de la pérdida de y 4) La importancia de la atención de la familia del paciente, 5) Comprender la necesidad de hablar de la muerte en la educación académica. Conclusión: Los resultados mostraron que los estudiantes no se sienten preparados para enfrentar la muerte, lo que demuestra un grado de ansiedad, inseguridad para hablar de ello, esto no es porque la discusión de este tema es frecuente en la graduación, creemos que la creación de espacios de auto-conocimiento, conciencia y reflexión sobre el tema de la muerte en las universidades, que permitiría la formación de profesionales no sólo es capaz de ver la vida para la rehabilitación o cura, sino también preparados para lidiar con la muerte. Descriptores: muerte; derecho a morir; educación en enfermería.